Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1001/jama.2013.285122
|View full text |Cite|
|
Sign up to set email alerts
|

Blood Pressure Trajectories in Early Adulthood and Subclinical Atherosclerosis in Middle Age

Abstract: IMPORTANCE Single measures of blood pressure (BP) levels are associated with the development of atherosclerosis; however, long-term patterns in BP and their effect on cardiovascular disease risk are poorly characterized.OBJECTIVES To identify common BP trajectories throughout early adulthood and to determine their association with presence of coronary artery calcification (CAC) during middle age. DESIGN, SETTING, AND PARTICIPANTSProspective cohort data from 4681 participants in the CARDIA study, who were black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
240
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(263 citation statements)
references
References 38 publications
(34 reference statements)
10
240
2
3
Order By: Relevance
“…Those studies identified 4 to 5 parallel trajectories in which trajectories with long-term higher blood pressure related to more cardiovascular pathology. [12][13][14] In our older population, we also observed that the class with a high midlife blood pressure had the highest risk of stroke and death compared with the class with the lowest blood pressure. However, a novel finding of our study is that the slope of increase was associated with an increasing risk of stroke and competing causes of death.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Those studies identified 4 to 5 parallel trajectories in which trajectories with long-term higher blood pressure related to more cardiovascular pathology. [12][13][14] In our older population, we also observed that the class with a high midlife blood pressure had the highest risk of stroke and death compared with the class with the lowest blood pressure. However, a novel finding of our study is that the slope of increase was associated with an increasing risk of stroke and competing causes of death.…”
Section: Discussionsupporting
confidence: 51%
“…Studies in young-and middle-aged adults showed that increases in blood pressure over long periods (10-30 years) are related to an increased risk of stroke and cardiovascular disease, [11][12][13] and that trajectories of higher blood pressure relate to a higher risk of subclinical atherosclerosis. 14 Trajectories in older people may vary even more because it is particularly in later ages that arterial stiffness increases, which is associated with increases in blood pressure and blood pressure variability. [15][16][17] Furthermore, studies suggest that lower blood pressures might also be harmful in this population, leading to an increased risk of myocardial infarction or death.…”
mentioning
confidence: 99%
“…We assessed the relationship between pattern of CVHS attainment through midlife to late life and AV disease in late life. As previously published,18 we identified trajectories of ideal cardiovascular health attainment through midlife to late life on the basis of CVHS at the 5 study visits using trajectory analysis22 with the use of the STATA macro TRAJ. We used the bayesian information criterion to decide the number of trajectories (2–5 trajectories assessed).…”
Section: Methodsmentioning
confidence: 99%
“…The BP indices used for the modeling included DBP, SBP, mean arterial pressure (MAP), and mean mid-BP (calculated as [SBP+DBP]/2, a marker of coronary heart disease risk among younger populations). 29,30 The following criteria were used to determine the number of BP trajectory groups and the trajectory shapes for each BP index 31,32 : (1) an a priori …”
mentioning
confidence: 99%
“…In recent years, the emerging application of multiple BP measurement-derived trajectories across the lifespan has provided insights for identifying novel means of preventing future cardiovascular risk. 30,32,38 Therefore, considering the dynamic nature of BP during pregnancy and the impact of seasonality on pregnancy BP levels, 39 BP trajectories that are an entire pregnancy course-dependent systemic approach have potential advantages over the fragmented, single BP measurement in terms of accuracy and reproducibility. Because all pregnant women should have at least 4 antenatal care assessments according to the new World Health Organization antenatal care model, 40 full utilization of these serial BP data would thus provide additional information for future risk stratification.…”
mentioning
confidence: 99%